Ratio Legis Policy of Republic of Indonesia State Police Regulation Number 8 of 2021 Based On Restorative Justice In Narcotics Crimes - Angga Wardana; Widhiana Suarda , I Gede; Azizah, Ainul (Dinasti Research, 2024)
Restorative justice, which is based on POLRI Regulation Number 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice, was formed to realize efforts to resolve criminal acts by prioritizing aspects of restorative justice. Through this regulation, criminal law enforcement by the police is oriented to re-emphasize the restoration of the original situation as before the crime occurred. The research method used uses a normative juridical research type with a statutory and regulatory approach. This research uses literature study techniques by inventorying suitability based on primary and secondary legal materials to answer the problems in this research. ratio legis implementation of the Republic of Indonesia State Police Regulation Number 8 of 2021 reflects a restorative justice approach in the investigation stage of handling criminal acts. It emphasizes the importance of healing and reconciliation as part of the investigative process, reflecting a paradigm shift in criminal law towards a more holistic and recovery-oriented approach. The dynamics of handling narcotics crimes based on the principles of restorative justice, there are special requirements that must be complied with. Republic of Indonesia State Police Regulation Number 8 of 2021 pays special attention to the condition of individuals involved in narcotics abuse. This consideration involves evaluating the status of drug users, the condition of the victim of drug abuse, the level of drug dependence of the perpetrator, the type of narcotics used, and the amount.